System identyfikacji wizualnej jako element tożsamości biblioteki akademickiej - Curyło, Monika (Biblioteka w chmurze czy chmury nad biblioteką, 2018)
The article presents the problem of creating and managing the brand of an academic library in the context of the university's identification system. Visual identity, understood as a mosaic of all visual messages, which facilitates recognition of a public institution, as well as brand awareness and development of long-term marketing strategies are the basic issues related to visual identification. The brand book (identity book), as well as printed and electronic materials, serve as a tool used to reinforce the institution's position on the market, and generate a coherent and logical system of symbols and connotations. The creation of a strong logo is one of the most important stages of building a corporate image, which has an ongoing influence on recipients and contributes to the success of a university and academic library brand.